Концепция липополисахарид-зависимого этиопатогенеза одонтогенных гнойно-воспалительных заболеваний челюстно-лицевой области - Морозова, М.Н. (Таврический медико-биологический вестник, 2010)
У роботi проаналiзованi даннi показникiв системи гомеостазу, дослiдженi у хворих на одонтогеннi абсцеси та флегмони, спираючись на якi запровонована нова концепцiя етiопатогенезу одонтогенних гнiйно-запальних захворювань, обумовлених впливом лiпополiцукориду грамнегативної мiкрофлори. The data of the parameters of the homeostasis system were analyzed in this work at patients with odontogenic abscesses and phlegmons. On the basis of this study the new concept of etiopathogenesis of the odontogenic purulent- inflamatory diseases was suggested which is due to the action of the lipopolysaccharide of the gram-negative microflora.